2010
DOI: 10.5851/kosfa.2010.30.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Chemical Composition, Textural Characteristics, and Sensory Properties of North and South Korean Native Chickens and Commercial Broilers

Abstract: The objective of this study was to compare the quality characteristics of chicken breast and thigh meat from North Korean native chickens (NKNC), South Korean native chickens (SKNC, woorimotdak), and commercial broilers (CB). NKNC thigh meat had a higher crude protein content than CB. In addition, the breasts of NKNC and CB had higher pH values than that of SKNC, but the cooking loss was higher in NKNC. The surface color of the breast and thigh meat of NKNC was darker and redder than that of SKNC and CB. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
55
2
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 18 publications
(23 reference statements)
11
55
2
6
Order By: Relevance
“…The authors explained that arachidonic acid can serve as a flavour enhancer by activating the TRPM5 cation channel, which is considered as a component of the sweet, bitter, and umami taste pathways of type II receptor cells. This is in agreement with other reports that higher sensory scores were observed for native chickens as compared to broilers which contained higher arachidonic acid content Jeon et al, 2010;Jung et al, 2011).…”
Section: Dietsupporting
confidence: 83%
“…The authors explained that arachidonic acid can serve as a flavour enhancer by activating the TRPM5 cation channel, which is considered as a component of the sweet, bitter, and umami taste pathways of type II receptor cells. This is in agreement with other reports that higher sensory scores were observed for native chickens as compared to broilers which contained higher arachidonic acid content Jeon et al, 2010;Jung et al, 2011).…”
Section: Dietsupporting
confidence: 83%
“…FA methyl esters were prepared from the extracted lipids with BF3-methanol (Sigma-Aldrich, St. Louis, MO, USA) and separated on a HP-6890N gas chromatograph (Hewlett-Packard, Palo Alto, CA, USA) as described previously (Jeon et al, 2010). A split inlet (split ratio, 50:1) was used to inject samples into a 30 m × 0.25 mm × 0.25 μm Omegawax 320 capillary column (Supelco, Bellefonte, PA, USA).…”
Section: Fa Analysismentioning
confidence: 99%
“…However, most of the researches have more focused on growth performance and carcass yield (Kim et al, 2010a;Kim et al, 2010b;Kim et al, 2012a;Kim et al, 2012b;Heo et al, 2013b;Hong et al, 2012). Since the factors affecting the flavor precursors in chicken meat have been studied extensively (Choi et al, 2010;Jayasena et al, 2013c;Jayasena et al, 2014;Jeon et al, 2010;Jung et al, 2011;Lee et al, 2012), it is worth to investigate the flavorrelated compounds in duck meat to develop a high quality meat-type duck breed. However, duck meat is different from chicken meat due to its muscle composition and it has been reported that different species have different flavor development mechanism (Ali et al, 2007;Mottram, 1998), and still, limited information is available regarding flavor-related compounds in duck meat.…”
Section: Introductionmentioning
confidence: 99%